Handbook of Movement Disorders - Chaudhuri, K Ray; Ondo, William G. (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2009)
Movement disorders are a complex group of disorders spanning all aspects of neurological illnesses and range from conditions characterized by too little movement (hypokinesis) to those where movement is excessive (hyperkinesis). The classic example would be Parkinson's disease, while other movement-related problems, such as tremor, chorea, dystonia, myoclonus, hemiballism and tics, occur in a range of inherited, drug-induced and sporadic disorders. Genetics plays an important part in the genesis of several conditions characterized by various movement disorders, such as Huntington's disease, dystonic conditions and myoclonus. Somatization from psychologically determined conditions can also manifest as movement disorders. Finally, sleep may be affected by movement disorders and a typical example would be restless legs syndrome. To non-experts, movement disorders may appear to be complex, sometimes bizarre and difficult to manage. Diagnosis is based mostly on observation and examination rather than radiology and serological assessments. This comp- hensive handbook deals with all the above movement disorders in a holistic manner, providing a detailed "snapshot" view of these complex disorders. As well as being useful to the general physician working in clinical settings where movement disorders often first present, such as accident and emergency depa- ments or in primary care, we hope that the up-to-date information will be useful for trainees and experts in the field of movement disorders. Chapter 1 Parkinson's disease Kartik Logishetty and K Ray Chaudhuri Introduction Parkinson's disease was first described by the London physician, James Parkinson, in 1817 and later named after him by Charcot.